Advances in the etiology, diagnosis, and treatment of intensive care unit-acquired weakness: a comprehensive narrative review - Zhang, Baorui; Zhai, Yuetong; Wang, Long; Shen, Aiping; Chen, Chang (Current Challenges in Thoracic Surgery, 2026)
Background and Objective: Intensive care unit-acquired weakness (ICU-AW) is a common complication in critically ill patients, characterized by generalized skeletal muscle weakness. It significantly prolongs the duration of mechanical ventilation and hospitalization, increases patient mortality, and leads to persistent impairment of long-term quality of life. This article provides a comprehensive review of the etiology, diagnosis, and multidisciplinary treatment of ICU-AW.Methods: A systematic literature search was performed in PubMed and Web of Science (1987–2026) to summarize current evidence on ICU-AW, with a focus on thoracic surgical patients.Key Content and Findings: Regarding etiology, this review focuses on dissecting the complex network formed by the interplay of systemic inflammatory responses, metabolic disturbances, direct neuromuscular injury, and iatrogenic factors. The diagnosis section systematically evaluates the application value and limitations of clinical assessment tools, electrophysiological examinations, and auxiliary means such as imaging and biomarkers. The treatment aspect emphasizes comprehensive management based on multidisciplinary collaboration, encompassing early rehabilitation training, neuromuscular electrical stimulation (NMES), individualized nutritional support, glycemic and metabolic regulation, and cautious optimization of medication use. In addition, the specific implications of ICU-AW for high‑risk surgical populations, including patients undergoing major thoracic surgery, are briefly discussed.Conclusions: This review aims to provide theoretical reference and practical guidance for the early clinical identification and effective intervention of ICU-AW and to outline future research directions to improve patient outcomes.